Leadership behaviors and coach-athlete relationships in Scandinavian coaches - Johansen, B. T.; Christensen, J. B.; Eoksen, E.; Fahlström, P. G.; Hageskog, C. A.; Høigaard, R. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Introduction The purpose of the study was to investigate in a sample of Scandinavian elite coaches, the relationship between perceptions of their own leadership behavior and their perception of the coach-athlete relationship. Method 149 elite coaches (e.g. national top and/or international level) from Denmark (n=50), Norway (n=50) and Sweden (n=49) participated (134 male, mean age 38.3±9.8yrs; 15 female, mean age 39.1±8.4). 58 percent of the coaches were coaches of individual sports and 42 percent were coaches of team sports. 59 percent of the participants had at some point, undertaken academic study related to sport at university level. A paper-copy questionnaires were distributed by post to all coaches listed in each country`s athletic federation index. Leadership behaviour: Coaches self reported their perceptions of their own leadership behaviors using the Leadership Scale for Sport (Chelladurai & Saleh, 1980). The Cronbach`s alpha for self reported leadership behavior was: .79 training and instruction, .59 positive feedback, .66 social support, .78 democratic behavior, and .46 autocratic. Coach-athlete relationship: The nature of the coach-athlete relationship was evaluated using the 13-item Nordic Coach-Athlete Relationship Questionnaire (NOR-CART-Q; Jowett & Ntoumanis, 2003). The Cronbach`s alpha for closeness, commitment, and complementarity was .83, .72 and .67 respectively. Results Positive feedback, training and instruction, and democratic behavior were the most frequent self-reported behavior subscales amongst the coaches. Moreover, it is a positive relationship between commitment and training and instruction (r=.25, p < 0.01) positive feedback (r= 22, p < 0.01) and social support behavior(r=.22 p < 0.01). Complementarity was positively related to training and instruction behavior (r=.17, p < 0.01). Multilevel logistic regression analyses indicated a significant difference between coaches in Denmark and Sweden on commitment (5.39 vs. 5.95) and complementarity (5.82 vs. 6.26) and coaches who are educated in sport use more positive feedback (4.25 vs. 4.41). Moreover, coaches with more than 10 years experiences in coaching us significantly more training and instruction (3.65 vs. 3.82) and social support (3.02 vs. 3.23) than coaches with less experiences. Furthermore, coaches in individual sport reported more democratic behavior (3.80 vs. 3.23) and less autocratic behavior (2.56 vs. 2.78) then coaches in team sport. Discussion In general coaches with more experience and more sport education used more positive feedback and social support. The study also revealed differences in leadership behavior between individual and team sport which is in line with former research.